A single-nanoparticle NO2 gas sensor constructed using active molecular plasmonics. Issue 7 (8th December 2014) - Chen, Lichan; Wu, Bo; Guo, Longhua; Tey, Ruiwen; Huang, Youju; Kim, Dong-Hwan
Abstract : A single-nanoparticle plasmonic sensor for the sensitive detection of gas molecules (NO2 ) has been constructed. Abstract : A single-nanoparticle plasmonic sensor for the sensitive detection of gas molecules (NO2 ) has been constructed. Taking advantage of active molecular plasmonics, the analyte selectively triggers a measurable spectral shift of ferrocene-modified single gold nanorods.